EFFECT OF ARTIFICIAL INSEMINATION OF QUEEN BEES ON EGG PRODUCTION IN FERGANA REGION (Scientific journal of the Fergana State University, 2022)
In order to increase the productivity of the bee family in the conditions of Uzbekistan, starting from early spring, it is necessary to organize a large number of artificial breeding of queen bees and their artificial fertilization, and during artificial fertilization of the queen bee, her reproductive organs Maturation period and effect on daily egg laying and how many eggs the queen lays after how many days are given